Safety Analysis of Aviation Flight-Deck Procedures Using Systemic Accident Model. Issue 19 (2016) - Hirose, Takayuki; Sawaragi, Tetsuo; Horiguchi, Yukio
Abstract: Analyzing the feasibility of procedures is important for ensuring safety when using systems that feature human operations and highly developed automation. This is certainly the case with flight-deck procedures due to their complexity, which sometimes leads to deviation from standard operation procedures (SOPs) and other serious outcomes (e.g., air crash accidents). To analyze the feasibility of procedures, we adopt the functional resonance analysis method (FRAM) (Hollganel, 2004) to examine the safety management of flight-deck procedures. However, FRAM is essentially a theoretic method, and there are currently no specific approaches or supportive tools to bridge the gap between theory and practice. In this paper, we propose an adaptation of the cognitive reliability and error analysis method (CREAM) (Hollnagel (1998)) that we call Fuzzy CREAM for systematic and quantitative FRAM analysis. We applied the proposed method to an actual air crash accident that occurred near Cali Airport, Colombia in 1995 and conclude that the accident was due to deviation from SOPs. On the basis of our analysis, we show that FRAM can identify potential hazardous paths that may lead to an accident. We also propose a new method using FRAM for pre-analysis of the safety of designed procedures.